Backlash Realism: The American Novel during the Long 1980s - Studer, Seth. (2017)
Abstract: Backlash Realism studies the limits of the novel: what can and cannot be represented in a novel, given the historico-structural architecture of the genre? How elastic is the genre? Where is its horizon? This dissertation focuses these questions by examining a specific literary-historical moment: the American novel during the waning years of postmodernism, a period I designate as "the long 1980s." This period follows what Mark McGurl has characterized as "the Program Era" and precedes the fiction of the new millennium. Consequently, this dissertation offers a prehistory of the present. Relying on conceptions of fictionality taken from Catherine Gallagher and Dorrit Cohn, and drawing on literary-sociological methods employed by scholars like McGurl, this dissertation traces a crisis of representation that faced American writers who sought to produce important novels during the 1980s, after decades of modernist and postmodernist experimentation had seemingly exhausted the possibility of innovation. In response to this crisis, many novelists discovered renewed interest in both realism as a mode of representation and the durability of "fictionality" when juxtaposed with fact. This dissertation first offers a historical-theoretical frame for this crisis and then examines several novelists - Gore Vidal, Don DeLillo, E.L. Doctorow, Tom Wolfe, Jonathan Franzen, and Nicholson Baker - whose quasirealist or neorealist projects can be characterized as "backlash" against postmodernism. This backlash coincided with the rise of neoliberalism and a broader cultural backlash against the political and social projects of the 1960s and '70s: in the United States, the so-called "Reagan Revolution." The metaphors or tropes that novelists like Vidal, Wolfe, and Franzen employed to debate and discuss the state of the novel after postmodernism borrowed language from contemporary anxieties over nationalism and national decline, urban decay, white flight, financialization, a return to the language of the market economy, and the AIDS epidemic. These novelists also reinvested heavily in a remarkably literal conception of realism, one that engaged heavily with factuality, privileged the universalized liberal subject, and eschewed paranoid hermeneutics. The resulting aesthetic proved influential for the fiction of the new millennium and produced useful tensions through which to understand and analyze the limits of novelistic representation.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of English.; Advisor: Ichiro Takayoshi.; Committee: Nathan Wolff, Joseph Litvak, and Andrew Hoberek.; Keywords: American literature, American studies, and American history.